Can we decrease the rate of negative sentinel lymph node biopsies? A retrospective study - Cassimjee, Ismail (My University, 2014)
The management of breast cancer has changed over the last century, with surgeries becoming less invasive and adjuvant therapies becoming indispensible. Sentinel lymph node biopsies (SLNB) have replaced axillary nodal dissections as a method of staging an axilla in early breast cancer. However, 70% of SLNBs are negative. The aim of this study was to determine if wecould decrease the rate of negative sentinel lymph node biopsies? A retrospective review over a 10 month period was undertaken. Patients undergoing a SLNB and who had a documented negative axillary ultrasound report were included. One hundred and fifty onepatients were eligible for inclusion. Patients’ ultrasound reports and initial biopsy specimen characteristics (ER/PR/Her2-neu, LVI, Grade, Location) were compared to their axillary nodal findings on histology. An ultrasound was able to predict a pathologically negative axilla in 71.6% of patients. Exclusion of micrometastasis increased the negative predictive value to82.8%. If the ultrasound was negative in a histologically positive axilla, it was likely that only 3 or less nodes were involved. Nodal metastasis could not be predicted based on the tumour characteristics that were reported on the initial tumour biopsy specimens(ER/PR/Her2- neu, LVI, Grade, Location). LVI and DCIS on the initial biopsy specimens were poorly correlated with the final histology specimen findings.. The results show that an ultrasound cannot currently replace a SLNB as an accurate means of evaluating an axilla. A clear limitation is the inability to detect micrometastasis, however the role of micrometastasis in axillary staging is diminishing. Ultrasonographic evaluation of the axilla is currently reported in a non-standardised manner. Classification systems do exist, and if applied to current reporting will increase the negative predictive value of ultrasonography. In the future, the combination of improved reporting standards of axillary ultrasounds, as well as the surgical conservatism with regard to the management of micrometastasis and small volume metastasis in the axilla will hopefully reduce the rate of negative SLNB’s.
Keywords: Biopsy; Breast Diseases--diagnosis